Differential Regulation of Soluble and Membrane-Bound Inorganic Pyrophosphatases in the Photosynthetic Bacterium Rhodospirillum rubrum Provides Insights into Pyrophosphate-Based Stress Bioenergetics - López-Marqués, Rosa L. (American Society for Microbiology, 2004)
Soluble and membrane-bound inorganic pyrophosphatases (sPPase and H(+)-PPase, respectively) of the purple nonsulfur bacterium Rhodospirillum rubrum are differentially regulated by environmental growth conditions. Both proteins and their transcripts were found in cells of anaerobic phototrophic batch cultures along all growth phases, although they displayed different time patterns. However, in aerobic cells that grow in the dark, which exhibited the highest growth rates, Northern and Western blot analyses as well as activity assays demonstrated high sPPase levels but no H(+)-PPase. It is noteworthy that H(+)-PPase is highly expressed in aerobic cells under acute salt stress (1 M NaCl). H(+)-PPase was also present in anaerobic cells growing at reduced rates in the dark under either fermentative or anaerobic respiratory conditions. Since H(+)-PPase was detected not only under all anaerobic growth conditions but also under salt stress in aerobiosis, the corresponding gene is not invariably repressed by oxygen. Primer extension analyses showed that, under all anaerobic conditions tested, the R. rubrum H(+)-PPase gene utilizes two activator-dependent tandem promoters, one with an FNR-like sequence motif and the other with a RegA motif, whereas in aerobiosis under salt stress, the H(+)-PPase gene is transcribed from two further tandem promoters involving other transcription factors. These results demonstrate a tight transcriptional regulation of the H(+)-PPase gene, which appears to be induced in response to a variety of environmental conditions, all of which constrain cell energetics.